A study on the awareness of the secondhand smoke (SHS) / Nur Arina Mohd Zin and Soleha Arshad - Mohd Zin, Nur Arina; Arshad, Soleha (Faculty of Administrative Science and Policy Studies, 2013)
This research provides information of the awareness on secondhand smoke case study in Jalan hang Tuah. Methods of collection data are primary and secondary data such as questionnaires, journals and also internet sources. The main objective of this research are to determine the most influential factors of awareness on secondhand smoke in Jalan Hang Tuah. The awareness on secondhand smoke (SHS) is determined by three independent variables. The environmental factors as like factors from the family, people surrounding the area does affecting the level of awareness on secondhand smoke. As similar to policy implemented this is the second factor that can affect the awareness of people towards the dangerous of secondhand smoke. Therefore, the independent variable will eventually contribute to people awareness on secondhand smoke. The sample of this study consists of 201 respondents which comprise of publics in Jalan Hang Tuah. This will help them gain awareness on secondhand smoke. Besides that, it will expose the public to be aware about negative impacts on secondhand smoke. Last but not least, the recommendations for future research is also have been discussed.